A Gold Needle Tip Array Ultrafast Electron Source with High Beam Quality - Brückner, Leon; Nauk, Constantin; Dienstbier, Philip; Gerner, Constanze; Löhrl, Bastian; Paschen, Timo; Hommelhoff, Peter (2024 37th International Vacuum Nanoelectronics Conference (IVNC), 2024)
Nanometer-sharp needle tips are the electron sources with the highest beam quality. However, for a single needle tip, the total emission current is limited. Combining multiple needles into an array of tips should allow for higher currents while preserving the properties of the individual emitters. Previous studies on tip arrays have shown impressive emission character-istics, but could not demonstrate favourable transversal beam properties such as a well-behaved spot shape or low emittance. Here, we introduce an ultrafast electron source composed of a lithographically fabricated array of nanometer-sharp gold tips illuminated by 25 fs laser pulses. By harnessing the emission of multiple needles, we achieve a high-current electron beam while preserving individual emitter properties. Our source delivers up to 2000 electrons per pulse at moderate laser peak intensities of 10 11 w /cm 2 , with a narrow energy width of 0.5 ± 0.05 eV and a well-behaved Gaussian profile. The resulting electron beam exhibits high collimation and a small normalized emittance on the order of nm.rad, making it ideal for applications requiring both high current and spatial resolution, such as free-electron light sources and chip-based particle accelerator

A Gold Needle Tip Array Ultrafast Electron Source with High Beam Quality - Brückner, Leon; Nauk, Constantin; Dienstbier, Philip; Gerner, Constanze; Löhrl, Bastian; Paschen, Timo; Hommelhoff, Peter (Nano Letters, 2024)
Electron sources are crucial elements in diverse applications such as electron microscopes, synchrotrons, and free-electron lasers. Nanometer-sharp needle tips are electron emitters with the highest beam quality, yet for a single needle the current is limited. Combining the emission of multiple needles promises large current yields while preserving the individual emitters’ favorable properties. We present an ultrafast electron source consisting of a lithographically fabricated array of sharp gold tips illuminated with 25 fs laser pulses. The source provides up to 2000 electrons per pulse for moderate laser peak intensities of 1011 W/cm2 and a narrow energy width of 0.5 ± 0.05 eV at low current. The electron beam has a well-behaved Gaussian profile and is highly collimated, yielding a small normalized emittance on the order of nm·rad. These properties are well suited for applications requiring both high current and spatial resolution, such as free-electron light sources and chip-based particle accelerators.<br
Keywords: nano-optics; ultrafast electron emission; field enhancement; lasers; electron sources

Atmospheric Plasma Spraying for Copper Coating of Ceramic Solid Electrolytes for Anode-Free Solid-State Batteries with Increased Interfacial Contact - Ockel, Manuela; Borchers, Andre; Fröhlich, Jan; Petersen, Matthias; Paschen, Timo; Christiansen, Silke; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Advances in solid-state battery technology are crucial for future energy storage solutions. Atmospheric plasma spraying (APS) offers a novel approach for producing copper coatings on ceramic solid electrolytes (SE) for anode-free solid-state batteries (AFSSBs), which generally promise increased safety and energy density. This study investigates the feasibility of APS for the fabrication of Cu-based current collectors with enhanced interfacial contact at the SE and high material deposition rates in comparison to physical or chemical vapor deposition of Cu. The qualitative results suggest that APS can produce Cu coatings with high interfacial contact without inducing high pressures through calendaring, which can lead to cracks in brittle solid electrolytes. This research addresses critical challenges in the production of AFSSBs with APS and evaluates the importance of tailored interface properties for optimized contact areas. The pressure induced by the accelerated particles is substantially lower compared to conventional calendaring tools. Surface characteristics of SE and coating were analyzed via laser scanning. SEM analysis showed several defects during splat formation, which reduces interfacial contact.<br

Coherent control at gold needle tips approaching the strong-field regime - Dienstbier, Philip; Paschen, Timo; Hommelhoff, Peter (Nanophotonics, 2021)
We demonstrate coherent control in photoemission from a gold needle tip using an ω − 2ω field composed of strong few-cycle laser pulses with a nearfield intensity of ∼4 TW/cm2. We obtain the nearfield intensity from electron energy spectra, showing the tell-tale plateau of field-driven electron rescattering at the metal surface induced by the fundamental field. Changing the relative phase between the fundamental field centered at 1560 nm and its second harmonic modulates the total emitted photocurrent with visibilities of up to 80% despite the strong and broadband excitation of the plasmonic material. Our work combines a two-color coherent control scheme and strong-field physics enabled by a nanoplasmonic emitte
Keywords: electron emission; gold needle tips; strong-field physics; two-color coherent control

Coherent control of two-color above-threshold photoemission from tungsten nanotips - Paschen, Timo; Förster, Michael; Krüger, Michael; Lemell, Christoph O; Wachter, G.; Libisch, Florian; Madlener, T.; Burgdorfer, J.; Hommelhoff, Peter (Journal of Physics: Conference Series, 2017)
Synopsis We demonstrate coherently controlled two-color above-threshold photoemission from a single crystal tungsten nanotip. With optimized fundamental and second harmonic intensities near perfect phase contrast can be obtained.
CRIS-Team Scopus Importer:2022-06-05

Electron Diagnostics for Extreme High Brightness Nano-Blade Field Emission Cathodes - Lawler, Gerard; Sanwalka, Kunal; Zhuang, Yumeng; Yu, Victor; Paschen, Timo; Robles, River; Williams, Oliver; Sakai, Yusuke; Naranjo, Brian; Rosenzweig, James (Instruments, 2019)
Electron beams are essential tools in modern science. They are ubiquitous in fields ranging from microscopy to the creation of coherent ultra-fast X-rays to lithography. To keep pace with demand, electron beam brightness must be continually increased. One of the main strategic aims of the Center for Bright Beams (CBB), a National Science Foundation Science and Technology Center, is to increase brightness from photocathodes by two orders of magnitude. Improving the state-of-the-art for photoemission-based cathodes is one possibility. Several factors have led to an alternative design becoming an increasing necessity; the nanoscale structure. Field emission sources from nano-tips would be an ideal candidate were it not for their low current and damage threshold. A 1-dimensional extended nano-fabricated blade, i.e., a projected tip, can solve the problems inherent in both designs. The novel geometry has been demonstrated to produce extremely high brightness electron beam bunches and is significantly more robust and easier to manufacture than traditional photocathodes. Theory indicates electron emission up to keV energies. We thus present a system of diagnostics capable of analyzing the cathodes and assessing their viability. The diagnostics are designed to measure the electron spectrum up to keV energies, with sub meV resolution at <100 eV, mean transverse energy (MTE), emission uniformity, and cathode lifetime. We also report preliminary data on total extracted charge and maximum detectable electron energy with a simplified retarding field spectromete
Keywords: diagnostics; electron spectrometer; nano-fabricated blade; electron source; high brightness

From strong-field physics in and at nanoscale matter to photonics-based laser accelerators - Kozak, Martin; Higuchi, Takuya; McNeur, Joshua; Shiloh, Roy; Heide, Christian; Paschen, Timo; Yousefi, Peyman; Sturm, Constanze; Li, Ang; Illmer, Johannes; Meier, Stefan; Schönenberger, Norbert; et al. (205, 2019)
New ways of controlling quasi-free and free electrons by means of phase-controlled ultrashort laser pulses are demonstrated: from strong-field physics in the conducting 2-d material graphene and at the surface of nanostructures, to laser acceleration of free electrons with a nanophotonic structure, and the demonstration of the longitudinal Kapitza-Dirac effec

Highly Localized Optical Field Enhancement at Neon Ion Sputtered Tungsten Nanotips - Paschen, Timo; Brückner, Leon; Wu, Mingjian; Spiecker, Erdmann; Hommelhoff, Peter (Nano Letters, 2023)
We present laser-driven rescattering of electrons at a nanometric protrusion (nanotip), which is fabricated with an in situ neon ion sputtering technique applied to a tungsten needle tip. Electron energy spectra obtained before and after the sputtering show rescattering features, such as a plateau and high-energy cutoff. Extracting the optical near-field enhancement in both cases, we observe a strong increase of more than 2-fold for the nanotip. Accompanying finite-difference time-domain (FDTD) simulations show a good match with the experimentally extracted near-field strengths. Additionally, high electric field localization for the nanotip is found. The combination of transmission electron microscope imaging of such nanotips and the determination of the near-field enhancement by electron rescattering represent a full characterization of the electric near-field of these intriguing electron emitters. Ultimately, nanotips as small as single nanometers can be produced, which is of utmost interest for electron diffraction experiments and low-emittance electron sources.<br

High-order above-threshold photoemission from nanotips controlled with two-color laser fields - Seiffert, Lennart; Paschen, Timo; Hommelhoff, Peter; Fennel, Thomas (Journal of the Physics B: Atomic and Molecular Physics, 2018)
We investigate the process of phase-controlled high-order above-threshold photoemission from metallic nanotips under bichromatic laser fields. Experimental photoelectron spectra resulting from two-color excitation with a moderately intense near-infrared fundamental field (1560 nm) and its weak second harmonic show a strong sensitivity on the relative phase and clear indications for a plateau-like structure that is attributed to elastic backscattering. To explore the relevant control mechanisms, characteristic features, and particular signatures from the near-field inhomogeneity, we performed systematic quantum simulations employing a one-dimensional nanotip model. Besides rich phase-dependent structures in the simulated above-threshold ionization photoelectron spectra we find ponderomotive shifts as well as substantial modifications of the rescattering cutoff as function of the decay length of the near-field. To explore the quantum or classical nature of the observed features and to discriminate the two-color effects stemming from electron propagation and from the ionization rate we compare the quantum results to classical trajectory simulations. We show that signatures from direct electrons as well as the modulations in the plateau region mainly stem from control of the ionization probability, while the modulation in the cutoff region can only be explained by the impact of the two-color field on the electron trajectory. Despite the complexity of the phase-dependent features that render two-color strong-field photoemission from nanotips intriguing for sub-cycle strong-field control, our findings support that the recollision features in the cutoff region provide a robust and reliable method to calibrate the relative two-color phas
Keywords: nanotips; coherent control; two-color; photoemission

High visibility in two-color above-threshold photoemission from tungsten nanotips in a coherent control scheme - Paschen, Timo; Förster, Michael; Krüger, Michael; Lemell, Christoph; Wachter, Georg; Libisch, Florian; Madlener, Thomas; Burgdörfer, Joachim; Hommelhoff, Peter (Journal of Modern Optics, 2017)
In this article, we present coherent control of above-threshold photoemission from a tungsten nanotip achieving nearly perfect modulation. Depending on the pulse delay between fundamental ((Formula presented.)) and second harmonic ((Formula presented.)) pulses of a femtosecond fiber laser at the nanotip, electron emission is significantly enhanced or depressed during temporal overlap. Electron emission is studied as a function of pulse delay, optical near-field intensities, DC bias field and final photoelectron energy. Under optimized conditions modulation amplitudes of the electron emission of 97.5% are achieved. Experimental observations are discussed in the framework of quantum-pathway interference supported by local density of states simulation
Keywords: density functional theory; electron emitter; Nanotip; two-color laser field

Nonadiabatic ponderomotive effects in photoemission from nanotips in intense midinfrared laser fields - Schoetz, Johannes; Mitra, Sambit; Fuest, Harald; Neuhaus, Marcel; Okell, William A.; Förster, Michael; Paschen, Timo; Ciappina, Marcelo F.; Yanagisawa, Hirofumi; Wnuk, Pawel; Hommelhoff, Peter; Kling, Matthias Friedrich (Physical Review A, 2018)
Transient near fields around metallic nanotips drive many applications, including the generation of ultrafast electron pulses and their use in electron microscopy. We have investigated the electron emission from a gold nanotip driven by midinfrared few-cycle laser pulses. We identify a low-energy peak in the kinetic energy spectrum and study its shift to higher energies with increasing laser intensities from 1.7 to 8.9×1011 W/cm2. The experimental observation of the upshift of the low-energy peak is compared to a simple model and numerical simulations, which show that the decay of the near field on a nanometer scale results in nonadiabatic transfer of the ponderomotive potential to the kinetic energy of emitted electrons and in turn to a shift of the peak. We derive an analytic expression for the nonadiabatic ponderomotive shift, which, after the previously found quenching of the quiver motion, com- pletes the understanding of the role of inhomogeneous fields in strong-field photoemission from nanostructures.

Strong-Field-Assisted Measurement of Near-Fields and Coherent Control of Photoemission at Nanometric Metal Tips - Förster, Michael; Paschen, Timo; Thomas, Sebastian; Krüger, Michael; Hommelhoff, Peter (Progress in Ultrafast Intense Laser Science, 2017)
Metal nanotips are an ideal testbed for ultrafast and strong-field physics at solids due to the superb control they allow over their very apex and the near-field at this apex that enhances an incident laser field. Particular attention has recently been devoted to the study of laser-induced electron emission from nanotips, where an enhanced fundamental understanding contributes to the implementation of nanotips as a source of femtosecond electron pulses. In this chapter we present photoemission studies at nanotips illuminated with femtosecond lasers. We demonstrate a new technique to measure the strength of near-fields at nanostructures by using our knowledge of the occurring strong-field physics. Electrons rescattering with the surface of the nanotip after emission give access to the prevalent near-field intensity on the nanometer scale. Our measurements fit well with independent simulations of Maxwell’s equations. In the second part we show that by employing a synthesized light field of a fundamental and a second harmonic laser pulse we achieve almost perfect coherent control of the photoemission process. We demonstrate that we can interpret our findings in terms of interfering quantum pathways.

Strong-field spectra and optical near-field enhancement at aluminium needle tips - Paschen, Timo; Nauk, Constantin; Dienstbier, Philip; Hommelhoff, Peter (Journal of Physics B: Atomic, Molecular and Optical Physics, 2021)
We study the rescattering of photoemitted electrons at aluminium needle tips. For various laser intensities we measure electron energy spectra to identify telltale features of strong-field rescattering, in particular a plateau with near-constant count rate and a high-energy cutoff. This rescattering process is used to investigate the geometry-dependent enhanced optical near-field at the apex of the aluminium tip. A large near-field enhancement, extracted from the spectral data, is supported by 3D finite-difference time-domain simulations. A systematic theoretical investigation of the near-field enhancement at aluminium tips shows a strong dependence on tip opening angle and radius of curvatur
Keywords: electron sources; aluminium needle tips; strong-field physics; rescattering; optical near-fields

Tracing attosecond electron emission from a nanometric metal tip - Dienstbier, Philip; Seiffert, Lennart; Paschen, Timo; Liehl, Andreas; Leitensdorfer, Alfred; Fennel, Thomas; Hommelhoff, Peter (Nature, 2023)
Solids exposed to intense electric fields release electrons through tunnelling. This fundamental quantum process lies at the heart of various applications, ranging from high brightness electron sources in d.c. operation to petahertz vacuum electronics in laser-driven operation. In the latter process, the electron wavepacket undergoes semiclassical dynamics in the strong oscillating laser field, similar to strong-field and attosecond physics in the gas phase. There, the subcycle electron dynamics has been determined with a stunning precision of tens of attoseconds, but at solids the quantum dynamics including the emission time window has so far not been measured. Here we show that two-colour modulation spectroscopy of backscattering electrons uncovers the suboptical-cycle strong-field emission dynamics from nanostructures, with attosecond precision. In our experiment, photoelectron spectra of electrons emitted from a sharp metallic tip are measured as function of the relative phase between the two colours. Projecting the solution of the time-dependent Schrödinger equation onto classical trajectories relates phase-dependent signatures in the spectra to the emission dynamics and yields an emission duration of 710 ± 30 attoseconds by matching the quantum model to the experiment. Our results open the door to the quantitative timing and precise active control of strong-field photoemission from solid state and other systems and have direct ramifications for diverse fields such as ultrafast electron sources, quantum degeneracy studies and sub-Poissonian electron beams, nanoplasmonics and petahertz electronics.
Keywords: Nanophotonics and plasmonics; Quantum mechanics; Ultrafast photonics

Two-color coherent control in photoemission from gold needle tips - Dienstbier, Philip; Paschen, Timo; Hommelhoff, Peter (Journal of Physics B: Atomic, Molecular and Optical Physics, 2021)
We demonstrate coherent control of photoemission from a gold needle tip using a two-color laser field. The relative phase between a fundamental field and its second harmonic imprints a strong modulation on the emitted photocurrent with up to 96.5% visibility. The visibility as a function of the second harmonic intensity can be described by three interfering quantum pathways. Increasing the bias voltage applied to the tip reduces the maximum achievable visibility and modifies the weights of the involved pathways. Simulations based on the time-dependent Schrödinger equation reproduce the characteristic cooperative signal and its dependence on the second harmonic intensity, which further confirms the involvement of three emission pathway
Keywords: Coheren control; gold needle tips; photoemission; quantum-pathway interference

Two-color coherent control of femtosecond above-threshold photoemission from a Tungsten nanotip - Förster, Michael; Paschen, Timo; Krüger, Michael; Lemell, Christoph; Wachter, Georg; Libisch, Florian; Madlener, Thomas; Burgdoerfer, Joachim; Hommelhoff, Peter (Physical Review Letters, 2016)
We demonstrate coherent control of multiphoton and above-threshold photoemission from a single solid-state nanoemitter driven by a fundamental and a weak second harmonic laser pulse. Depending on the relative phase of the two pulses, electron emission is modulated with a contrast of the oscillating current signal of up to 94%. Electron spectra reveal that all observed photon orders are affected simultaneously and similarly. We confirm that photoemission takes place within 10 fs. Accompanying simulations indicate that the current modulation with its large contrast results from two interfering quantum pathways leading to electron emissio

Two-color phase-controlled photoemission from a zero-dimensional nanostructure - Paschen, Timo; Förster, Michael; Krüger, Michael; Lemell, Christoph; Wachter, Georg; Libisch, Florian; Madlener, Thomas; Burgdoerfer, Joachim; Hommelhoff, Peter (205, 2019)
We demonstrate that multi-photon photoemission including above-threshold multiphoton orders from a nanotip can be coherently controlled with the optical phase between two light fields. By focusing 74 fs drive pulses at 1560 nm and their second harmonic at 780 nm onto the tip and changing the optical phase between the two colors, we observe an emission current modulation of up to 97.5 %. Additionally, electron energy spectra reveal a homogeneous modulation of all multiphoton orders. Hence, the electron current can be strongly increased (by a factor of 3.7) or almost completely turned off due to interference between two different quantum channels in the material. We argue that the extremely high degree of coherence evidenced by this near-unity current modulation depth is due to the confinement of the local field enhancement at the nanotip. The nano-rod effect allows to apply large DC fields, adding a further degree of freedom to investigate the modulation contrast of the photoemitted electron yield. We show that for an increasing DC electric field a non-cooperative distribution of electron emission leads to a decrease in modulation contras

Ultrafast Strong-Field Electron Emission and Collective Effects at a One-Dimensional Nanostructure - Paschen, Timo; Roussel, Ryan; Seiffert, Lennart; Kruse, Björn; Heide, Christian; Dienstbier, Philip; Mann, Joshua; Rosenzweig, James; Fennel, Thomas; Hommelhoff, Peter (ACS Photonics, 2023)
Enhanced near-fields at metallic nanostructures enable the generation of ultrafast nanometric electron pulses and the investigation of fundamental ultrafast dynamics in electron emission. Here we show strong-field induced photoemission from a nanometer-sharp tungsten-covered silicon nanoblade and report the systematic measurement of intensity-dependent electron energy spectra and yields. The observed plateau and cutoff features in the electron spectra indicate the presence of elastic electron rescattering in the enhanced near-fields at the surface of the one-dimensional nanostructure. For the first time, we can hence observe strong-field features from a one-dimensional object, as opposed to zero-dimensional needle tips employed so far. A comparison with results from classical and quantum simulations reveals that the extended geometry of the nanoblades and a cascaded near-field enhancement due to surface roughness leads to a broad energy distribution and high electron energies. A systematic analysis of the electron yield demonstrates nonlinear photoemission at moderate laser intensities and a clear transition to a regime with linear intensity dependence. This distinct feature is interpreted as the onset of space-charge trapping. The presented one-dimensional nanostructure enables us to generate above keV electrons without noticeable target damage and more than 13000 electrons per laser pulse, which is of utmost interest for novel classes of ultrafast photocathodes.
CRIS-Team Scopus Importer:2023-03-03
Keywords: FDTD; one-dimensional; photoemission; space-charge; strong-field; TDSE; ultrafast